The preparation, characterization, and pharmacokinetic studies of chitosan nanoparticles loaded with paclitaxel/dimethyl-β-cyclodextrin inclusion complexes - Ye YJ (Dove Medical Press, 2015)
Ya-Jing Ye,1 Yun Wang,1 Kai-Yan Lou,1 Yan-Zuo Chen,1 Rongjun Chen,2 Feng Gao1,3,4 1Department of Pharmaceutics, School of Pharmacy, East China University of Science and Technology, Shanghai, People’s Republic of China; 2Department of Chemical Engineering, Imperial College London, London, United Kingdom; 3Shanghai Key Laboratory of Functional Materials Chemistry, 4Shanghai Key Laboratory of New Drug Design, East China University of Science and Technology, Shanghai, People’s Republic of China Abstract: A novel biocompatible and biodegradable drug-delivery nanoparticle (NP) has been developed to minimize the severe side effects of the poorly water-soluble anticancer drug paclitaxel (PTX) for clinical use. PTX was loaded into the hydrophobic cavity of a hydrophilic cyclodextrin derivative, heptakis (2,6-di-O-methyl)-β-cyclodextrin (DM-β-CD), using an aqueous solution-stirring method followed by lyophilization. The resulting PTX/DM-β-CD inclusion complex dramatically enhanced the solubility of PTX in water and was directly incorporated into chitosan (CS) to form NPs (with a size of 323.9–407.8 nm in diameter) using an ionic gelation method. The formed NPs had a zeta potential of +15.9–23.3 mV and showed high colloidal stability. With the same weight ratio of PTX to CS of 0.7, the loading efficiency of the PTX/DM-β-CD inclusion complex-loaded CS NPs was 30.3-fold higher than that of the PTX-loaded CS NPs. Moreover, it is notable that PTX was released from the DM-β-CD/CS NPs in a sustained-release manner. The pharmacokinetic studies revealed that, compared with reference formulation (Taxol®), the PTX/DM-β-CD inclusion complex-loaded CS NPs exhibited a significant increase in AUC0→24h (the area under the plasma drug concentration–time curve over the period of 24 hours) and mean residence time by 2.7-fold and 1.4-fold, respectively. Therefore, the novel drug/DM-β-CD inclusion complex-loaded CS NPs have promising applications for the significantly improved delivery and controlled release of the poorly water-soluble drug PTX or its derivatives, thus possibly leading to enhanced therapeutic efficacy and less severe side effects. Keywords: dimethyl-β-cyclodextrin, inclusion complex, chitosan nanoparticles, drug delivery, sustained release, paclitaxel